Nyanggem - Fitria Kurniasari (Institut Seni Indonesia Yogyakarta, 2018)
Composition called nyanggem or in terms of another nyarios in language Sunda which means talk is a form of music resulting from logat, using a way that is at jangka and wirahma, then logat the conversation someone will be able as melody.Composition is expected to to be an early stage to make logat as one of objects could become work better. But based on logat in west java, composition it also took the story the author personal about mom have a struggle to become the backbone of family.